2023
DOI: 10.3390/foods12132489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 60Co Irradiation on Volatile Components of Turmeric (Curcumae Longae Rhizoma) Volatile Oil with GC–IMS

Abstract: 60Co irradiation is an efficient and rapid sterilization method. The aim of this work is to determine the changes in essential-oil composition under different irradiation intensities of 60Co and to select an appropriate irradiation dose with GC–IMS. Dosages of 0, 5, and 10 kGy of 60Co were used to analyze turmeric (Curcumae Longae Rhizoma) volatile oil after 60Co irradiation (named JH-1, JH-2, and JH-3). The odor fingerprints of volatile organic compounds in different turmeric volatile oil samples were constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is particularly suitable for heat-sensitive and volatile products. Radiation sterilization has been widely used in foods and Chinese medicinal materials [11][12][13].…”
Section: Saturated Steam Sterilizationmentioning
confidence: 99%
“…It is particularly suitable for heat-sensitive and volatile products. Radiation sterilization has been widely used in foods and Chinese medicinal materials [11][12][13].…”
Section: Saturated Steam Sterilizationmentioning
confidence: 99%
“…The study proved that the chemometric-based models facilitate data-driven decisions to optimize food quality, ensuring that the product meets consumer demands and regulatory standards. In addition, He et al [10] evaluated the impact of 60 Co irradiation on turmeric essential oil composition using gas chromatography-ion mobility spectrometry (GC-IMS). The findings demonstrated that, even though compound composition remained constant, the peak intensities were altered, supporting a 5 kGy/min irradiation dose for preserving essential oil quality.…”
mentioning
confidence: 99%